The Impact of Inflation, World Oil Prices, and the Rupiah Exchange Rate on Sectoral Stock Index Returns in the Indonesia Stock Exchange - Arya Firma Arifin; Maulana Ikhrom Ababil; Rafif Putra W; Leonardus Reynhard Peri; Maria Yovita R. Pandin (Indonesian Journal Publisher, 2025)
This study examines the effects of inflation (X1), global crude oil prices (X2), and the rupiah exchange rate (X3) on sectoral stock index returns (Y) in the energy sector listed on the Indonesia Stock Exchange. This research employs a quantitative approach using secondary data obtained from Bank Indonesia, the Indonesia Stock Exchange, and Investing.com over a five-year period. Multiple linear regression analysis was conducted using SPSS to evaluate both partial and simultaneous effects of the independent variables on stock index returns. The results show that inflation has a negative but statistically insignificant effect on sectoral stock index returns, while global crude oil prices exhibit a positive yet insignificant influence. In contrast, the rupiah exchange rate has a positive and statistically significant effect on sectoral stock index returns. These findings indicate that exchange rate movements play a dominant role in explaining return variability in the energy sector. Therefore, investors and policymakers should pay close attention to exchange rate stability when making investment and economic policy decisions.